An assessment of how brand awareness influences brand recognition throught product placement, applied to the automotive industry and computers - Drumond, Daniel Sousa (2017)
In an era where traditional forms of communication have been losing their effectiveness due to consumer saturation, marketers have been looking for alternative ways to reach their target. Therefore, in a scenario where brands compete fiercely to be seen, heard, but especially remembered in consumers’ minds, product placement presents itself as an attractive and distinctive alternative to be explored. Despite the growth of product placement in recent years, most empirical studies focus solely on assessing viewers recall and attitudes towards product placement. Thus, this research further contributes to existing literature by introducing the dimension of brand recognition. Moreover, it will direct its focus towards cars and computers product placement within movies, allowing for new and unique insights. This procedure also allows for an interesting segmentation of the distinct group of consumers which are likely to recognize brands in this context. The present research is quantitative natured and comprises a brand awareness test and a brand recognition experiment. The brand awareness test allowed to group the brands into three distinct groups of awareness: top-of-mind, spontaneous awareness and the lowest level of awareness (Aaker, 1991). While the brand recognition experiment aimed to study consumers’ ability to identify the brand’s name through visual cues and other brand attributes. The results suggest that there is a direct relationship between brand awareness and brand recognition in both product categories analyzed. It was also possible to identify profiles of brand recognition considering socio-demographic characteristics, viewing frequency of movies, knowledge of the product category, and consumer’s attitude towards product placement.